MAKNA LIRIK LAGU TRADISONAL ANAK-ANAK AMEFURI (KAJIAN SEMIOTIKA) - Afifah, Hasna Aufa (Ayumi : Jurnal Budaya, Bahasa, dan Sastra, 2017)
Traditional Japanese songs hold many deep meanings. This research discusses (1) the meaning of icon, indexes, symbols on the song of Amefuri, and (2) the meaning contained therein. The theory of Peirce Semiotic Amefuri is used because one of traditional song of Japanese children protected by the state. This research shows that the song Amefuri has 1 icon, 5 indexes, and 1 simbol, and based on the icon, index, and symbol, it shows that Amefuri song has affection meaning. Keyword: Amefuri, meaning, semiotics